2007
DOI: 10.1080/18811248.2007.9711287
|View full text |Cite
|
Sign up to set email alerts
|

Research and Development of Minor Actinide-containing Fuel and Target in a Future Integrated Closed Cycle System

Abstract: ÃÃResearch and development of minor actinide-containing fuels and targets, i.e., (Pu,Am)O 2 -MgO, (Pu,Np)O 2 -MgO, (U,Pu,Np)O 2 , (U,Pu,Np)N and (Pu,Np,Zr)N, for use in a future integrated closed cycle system that includes fast reactor and accelerator driven sub-critical system is underway. The present statuses of fabrication test and property measurements are given. Design concept of the oxide target is described in detail together with a screening of the support material. A new apparatus for the measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Assessing a pellet as a function of temperature and irradiation history is a minimum performance standard. The metallic form is the best choice because it generally has high melting point and the space volume for loading can be minimized 50 . Thus, we have chose metallic forms for 79 Se, 93 Zr, 99 Tc and 107 Pd.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessing a pellet as a function of temperature and irradiation history is a minimum performance standard. The metallic form is the best choice because it generally has high melting point and the space volume for loading can be minimized 50 . Thus, we have chose metallic forms for 79 Se, 93 Zr, 99 Tc and 107 Pd.…”
Section: Methodsmentioning
confidence: 99%
“…The pellets containing these metals were simulated as a homogeneous mixture with the moderator material, YD 2 . For I, our previous study showed that BaI 2 is the most suitable compound because of its chemical stability and easy manufacturing 50 . For Cs, many Cs compounds have been proposed 51 .…”
Section: Methodsmentioning
confidence: 99%
“…Without isotopic separation, such compositions were used as the initial compositions of the LLFPs in the pins. All LLFPs were considered in metallic forms because their melting points are generally high, and the space volume for loading can be minimized 34 . The LLFPs are supposed to be dispersed homogeneously in the pins, which helps to transmute the LLFPs 35 4) and may result in a significant transmutation.…”
Section: Selection Of Llfpsmentioning
confidence: 99%
“…Such a system could reduce the capacity of the TRU burner units and the associated fuel cycle facilities to about 1/5 and 1/8, respectively. ere have been many studies on uranium-free or fertile-free fuel systems [1][2][3]; however, difficulties remain, such as the requirement for new reprocessing technology. For example, reprocessing technology for producing TRU-burning oxide fuel is required to separate actinides and lanthanides, which have similar chemical behavior [4].…”
Section: Introductionmentioning
confidence: 99%